Identification the Structure of the Waste Supply Chain for Circular Economy: Case Study in Pangkalan Kerinci - Nasirly, Riri; Komariah , Yeni (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Keeping the materials at their highest value for as long as possible through reusing and recycling the waste, was the most applicable method for waste elimination, an application of the circular economy concept in Indonesia. The problem in waste management in Pangkalan Kerinci is, that during the transport and treatment to the landfill area, the waste is not sorted and mixed yet. This study uses a descriptive method with a qualitative approach. The study found that the town of Pangkalan Kerinci Environmental service have serve 72% of the town area, using 19 vehicles (dumping truck), 19 routes for trash collection, 4 collapsible vehicles (bin container truck), and motorcycles for non-accessible locations. Problems found in waste management in Pangkalan Kerinci are; the lack of waste banks and garbage bins, lack of personnel in transporting and sorting, lack of excavators in the landfill facility, and the short supply of dump trucks and trash collecting vehicles